2016
DOI: 10.1186/s40064-016-2683-6
|View full text |Cite
|
Sign up to set email alerts
|

Decoding options and accuracy of translation of developmentally regulated UUA codon in Streptomyces: bioinformatic analysis

Abstract: BackgroundThe gene bldA for leucyl is known for almost 30 years as a key regulator of morphogenesis and secondary metabolism in genus Streptomyces. Codon UUA is the rarest one in Streptomyces genomes and is present exclusively in genes with auxiliary functions. Delayed accumulation of translation-competent is believed to confine the expression of UUA-containing transcripts to stationary phase. Implicit to the regulatory function of UUA codon is the assumption about high accuracy of its translation, e.g. the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Although hypotheses on the role of PTTMs in bldA ‐mediated regulation were proposed immediately after the discovery that bldA is a tRNA gene (Lawlor et al , ), no further studies in this direction have been undertaken. Recently, we have shown that several Streptomyces strains carry an extensive repertoire of PTTM genes, including those for A37 hypermodification (Rokytskyy et al , ); we also provided initial evidence that reduced level of MiaB‐mediated PTTM affects Streptomyces biology (Sehin et al , ). The latter work has been carried out on transposon mutant of Streptomyces ghanaensis ATCC14672 and left many questions unanswered because of low genetic tractability of ATCC14672.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Although hypotheses on the role of PTTMs in bldA ‐mediated regulation were proposed immediately after the discovery that bldA is a tRNA gene (Lawlor et al , ), no further studies in this direction have been undertaken. Recently, we have shown that several Streptomyces strains carry an extensive repertoire of PTTM genes, including those for A37 hypermodification (Rokytskyy et al , ); we also provided initial evidence that reduced level of MiaB‐mediated PTTM affects Streptomyces biology (Sehin et al , ). The latter work has been carried out on transposon mutant of Streptomyces ghanaensis ATCC14672 and left many questions unanswered because of low genetic tractability of ATCC14672.…”
Section: Introductionmentioning
confidence: 53%
“…Based on previous data (Rokytskyy et al , ) we focused on S. albus genes XNR_1074 and XNR_1078 (hereafter referred to as miaA and miaB respectively) that encode orthologs of the MiaA and MiaB proteins from proteobacteria. Location of miaA and miaB in S. albus genome is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed for S. albus J1074 a specialized codon reporter system based on S. coelicolor A number of recent studies suggest that it is not the delayed expression of bldA gene but formation of mature (translationally competent) tRNA holds the key to its regulatory function (Leskiw et al 1991;Xu et al 2008;Pettersson and Kirsebom 2011). Yet, besides initial in silico predictions (Rokytskyy et al 2016) nothing is known about genetics of tRNA maturation in Streptomyces. Likewise, there is growing body of data on crucial role of environmental factors in tRNA biology (Laxman et al 2013;Moukadiri et al 2014;Sakai et al 2016), although this area remains unexplored in case of bldA gene.…”
Section: Discussionmentioning
confidence: 99%
“…Mistranslation of UUA is usually invoked as the most plausible explanation of such observation. Our recent in silico study provided some support in favor of mistranslation hypothesis [15]. However, there is no model system for Streptomyces which would provide simple experimental framework to observe and probe mistranslation.…”
mentioning
confidence: 88%